Complex assessment of the level and dynamics of the agrarian capacity of the Khmelnytskyi Region - Hryhoruk, Pavlo; Makarov, Andrii (The Journal of V. N. Karazin Kharkiv National University. Series: International Relations. Economics. Country Studies. Tourism, 2019)
Management of agricultural production in a market environment requires continuous improvement of approaches and methods for solving this problem. Strategic and tactical planning becomes a part of effective management of a market economy and deserves special attention. Adoption of grounded managerial decisions in the agrarian sector economy requires the identification of a comprehensive quantitative assessment of the capacity that will contribute to the identification of promising goals and the development of a rational strategy for their achievement. The given task can be solved by using the toolkit of economic and mathematical modeling, in particular the methodology of integral assessment. The subject of the study in the article is the toolkit for a comprehensive assessment of agrarian capacity. The aim of the article is to calculate and identify the level of agricultural capacity of the Khmelnytskyi region, analyze its dynamics and identify trends in its change. The common scientific methods are used like system analysis – for identifying components of agrarian capacity; statistical analysis – for identifying dynamics of agrarian capacity components; method of integral index – to identify the level of agrarian capacity; method of comparison – for assessing efficiency of use of capacity. The results are obtained: the assessment of agrarian capacity of Khmelnytskyi region during 2012-2016is carried out; trends of changing it components are analyzed; the effectiveness of it use is studied; It was found out that mainly the activities of the agrarian sector are ensured through the effective use of resources. Conclusions: calculated assesses of agrarian capacity end trends of it changes are proposed to take into account by State Bodies of Khmelnytskyi region when the strategy of social and economic development is created and improved.